Perekrutan di negara ketiga: Kasus Pekerja Filipina Luar Negeri di Taiwan hingga Polandia - Anna Joceline Dizon Ituriaga (Badan Strategi Kebijakan Hukum, 2024)
This study explores the complexities of third-country serial labor migration among Filipino factory workers, specifically those moving from Taiwan to Poland